2020
DOI: 10.1038/s41594-020-00532-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into outer membrane asymmetry maintenance in Gram-negative bacteria by MlaFEDB

Abstract: The asymmetric phospholipid outer membrane (OM) of Gram-negative bacteria serves as the first line of defense against cytotoxic substances such as antibiotics. The Mla pathway is known to maintain the lipid asymmetry of the OM by transporting phospholipids between the inner and outer membranes. Six Mla proteins MlaFEDBCA are involved, with the ABC transporter MlaFEDB acts through a mechanism yet to be elucidated. Here we determine cryo-EM structures of MlaFEDB in apo, phospholipid-, ADP-or AMP-PNP-bound state … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 64 publications
9
83
3
Order By: Relevance
“…Moreover, the export of de novo synthesized phospholipids to the outer membrane during cell growth might be driven by Mla (35). The Mla system consists of an MlaFEDB complex in the inner membrane, MlaA-porin in the outer membrane, and the shuttle on May 9, 2021 by guest http://aac.asm.org/ Downloaded from protein MlaC in the periplasmic region (35)(36)(37). MlaF interacts with MlaB, to comprise the cytoplasmic portion of the MlaFEDB complex (44), which drives phospholipid trafficking across the bacterial envelope to maintain outer membrane integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the export of de novo synthesized phospholipids to the outer membrane during cell growth might be driven by Mla (35). The Mla system consists of an MlaFEDB complex in the inner membrane, MlaA-porin in the outer membrane, and the shuttle on May 9, 2021 by guest http://aac.asm.org/ Downloaded from protein MlaC in the periplasmic region (35)(36)(37). MlaF interacts with MlaB, to comprise the cytoplasmic portion of the MlaFEDB complex (44), which drives phospholipid trafficking across the bacterial envelope to maintain outer membrane integrity.…”
Section: Discussionmentioning
confidence: 99%
“…This ensues the reversible partitioning of the PL molecule(s) between the lipid binding pockets of MlaC and the complex, even in the absence of ATP. While MlaD hexamers alone bind PLs much less strongly than MlaC (15), the MlaFEDB complex, where several structures now reveal a combined lipid binding cavity formed by both MlaD and MlaE (19)(20)(21)(22)(23), must possess strong affinity for PLs, likely comparable to MlaC. The trajectory of PL movement between the two binding sites remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, high sensitivity imparted by the use of [ 14 C]-labelled lipids allowed us to identify the key role ATP hydrolysis play in ultimately driving PL transport in the retrograde fashion. In the midst of preparing this manuscript, Tang et al have independently developed an indirect assay using non-native fluorescent lipids, and similarly reported that the Mla pathway mediates ATP-dependent retrograde PL transport in vitro (20). While they did not detect the spontaneous retrograde step, our complementary assays collectively establish the directionality of the system.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting debate as to whether the Mla system drives retrograde versus anterograde phospholipid transport has called for the reconstitution of the inner and outer membrane Mla components into proteoliposomes, as was achieved previously for the lipopolysaccharide (LPS) transport system 1 . In this issue of Nature Structural & Molecular Biology, Tang et al 2 report a high resolution cryo-EM structure of the Mla inner membrane ABC transporter complex. The authors also reconstitute the entire Mla system into inner and outer membrane proteoliposomes.…”
Section: Russell E Bishopmentioning
confidence: 99%